2022
DOI: 10.1002/cam4.5511
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell vaccines improve the glioma microenvironment: Influence, challenges, and future directions

Abstract: Introduction Gliomas, especially the glioblastomas, are one of the most aggressive intracranial tumors with poor prognosis. This might be explained by the heterogeneity of tumor cells and the inhibitory immunological microenvironment. Dendritic cells (DCs), as the most potent in vivo functional antigen‐presenting cells, link innate immunity with adaptive immunity. However, their function is suppressed in gliomas. Therefore, overcoming the dysfunction of DCs in the TME might be critical to treat gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 127 publications
0
15
0
Order By: Relevance
“…27,28 Many of the cytokines involved in the pathogenesis of Tumor microenvironment and immune cell infiltration have gradually been regarded as hotspots in glioma and they could be used to predict patents' prognosis or immune responses. 29,30 Wang et al revealed the immunosuppressive microenvironment roles of Podoplanin (PDPN) in glioma with IDH wildtype. 31 Zhang et al successfully established a tryptophan metabolism-based model in glioma to predict these patients' prognosis and immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Many of the cytokines involved in the pathogenesis of Tumor microenvironment and immune cell infiltration have gradually been regarded as hotspots in glioma and they could be used to predict patents' prognosis or immune responses. 29,30 Wang et al revealed the immunosuppressive microenvironment roles of Podoplanin (PDPN) in glioma with IDH wildtype. 31 Zhang et al successfully established a tryptophan metabolism-based model in glioma to predict these patients' prognosis and immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironment and immune cell infiltration have gradually been regarded as hotspots in glioma and they could be used to predict patents’ prognosis or immune responses 29,30 . Wang et al revealed the immunosuppressive microenvironment roles of Podoplanin (PDPN) in glioma with IDH wildtype 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are extremely important for the induction of acquired immunity, also influencing the lymphocytic response, its differentiation, and antigen presentation. With this in mind, within GBM pictures, DCs are found with reduced function, being in an inhibited or immature state, which can be related to the severe tumor microenvironment, DCs are kept with low function due to the inhibitory effect of the immune microenvironment, and this status is problematic for body function, but reversed by DC vaccines[ 147 ]. This is due to the fact that the advantages of DCs vaccines are based on in vitro matured dendritic cells, usually from the affected individual himself, which can activate previously inhibited Ts lymphocytes, increasing the patient's adaptive response, increasing the expression of MHCs, cytokines and chemokines, and promoting an intense migration of immune cells to the immunosuppressive microenvironment found in GBM[ 147 ].…”
Section: Vaccine-based Therapymentioning
confidence: 99%
“…The whole tumor lysates contain a variety of tumor antigens, such as TSAs. However, other unrelated antigens are also present in the tumor lysates, resulting in decreased specificity that hinders antigens processing and presentation of DCs [ 21 ]. Peptide- or protein-based DC vaccines can reduce the incidence of autoimmune-related adverse reactions while maintaining tumor selectivity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%